2024
DOI: 10.1002/prca.202300035
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of novel biomarkers for frailty diagnosis via serum amino acids metabolomic analysis using UPLC‐MS/MS

Mengyuan Zhou,
Wenjing Sun,
Jiaojiao Chu
et al.

Abstract: PurposeThis study was aimed to analyze serum amino acid metabolite profiles in frailty patients, gain a better understanding of the metabolic mechanisms in frailty, and assess the diagnostic value of metabolomics‐based biomarkers of frailty.Experimental DesignThis study utilized the ultra‐performance liquid chromatography tandem mass spectrometry to examine amino acids associated with frailty. Additionally, we employed multivariate statistical methods, metabolomic data analysis, receiver operating characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…One study showed a 34.3% increase of serum kynurenine in people with frailty compared to those considered pre-frail ( Jang et al, 2020 ). A recent study identified kynurenine in combination with cysteine, glutamine, citrulline, tyrosine, and phenylalanine as potential diagnostic biomarkers for frailty ( Zhou et al, 2024 ). Additionally, many studies have suggested that kynurenine induces cytotoxicity in other cells and tissues such as neuronal and chronic pain ( Jovanovic et al, 2020 ), renal ( Addi et al, 2018 ), major depressive disorder in females ( Zhou et al, 2019 ) and retinal disease ( Rejdak et al, 2011 ).…”
Section: Metabolomics and Frailtymentioning
confidence: 99%
“…One study showed a 34.3% increase of serum kynurenine in people with frailty compared to those considered pre-frail ( Jang et al, 2020 ). A recent study identified kynurenine in combination with cysteine, glutamine, citrulline, tyrosine, and phenylalanine as potential diagnostic biomarkers for frailty ( Zhou et al, 2024 ). Additionally, many studies have suggested that kynurenine induces cytotoxicity in other cells and tissues such as neuronal and chronic pain ( Jovanovic et al, 2020 ), renal ( Addi et al, 2018 ), major depressive disorder in females ( Zhou et al, 2019 ) and retinal disease ( Rejdak et al, 2011 ).…”
Section: Metabolomics and Frailtymentioning
confidence: 99%